A Survey of SME Accounting and Reporting Practices in Austria - Lindner, Bernhard; Hoelzl, Kerstin (World Bank, Vienna, 2016)
This report gives an overview of the key results from the analysis of the data collected in a survey conducted in October and November 2012 by the Austrian Institute for small and medium enterprise (SME) research on behalf of the World Bank center for financial reporting reform (CFRR). The survey was carried out using an online questionnaire and captures data from more than 780 SMEs that are representative of the Austrian SME sector. The primary purpose of this report is to assist the accounting and auditing profession, policy makers, and users of financial information in understanding the value and the constraints of SMEs’ financial reporting practices. It also feeds into a broader CFRR study on corporate financial reporting reform in Austria. The report presents the results of the survey grouped by topical areas as follows: accounting practices in Austrian SMEs; auditing financial statements; SME financing; and financial reporting and access to finance.